AB0520 Long-term efficacy of adalimumab and etanercept in psoriatic arthritis patients: prolonged intervals between injections. (23rd January 2014) - Lorenzin, M.; Ramonda, R.; Modesti, V.; Ortolan, A.; Frallonardo, P.; Punzi, L.
Abstract : Background: Psoriatic arthritis (PsA) is a progressive chronic inflammatory disease which affects both the axial and peripheral joints and often causes patient impairment; patients function and health-related quality of life could be compromised. Following the introduction of anti tumor necrosis factor-α (TNFα) agents in the treatment of active spondyloarthritis, several aspects including disease activity, spinal mobility, peripheral arthritis and enthesitis as well as quality of-life have improved considerably. Objectives: The aim of this study was to evaluate the long-term efficacy of adalimumab and etanercept treatment in clinical practice in PsA patients and to assess the percentage of patients with progressive lengthening of therapy interval administration in the event of optimal treatment response. Methods: A retrospective study was carried out on 127 PsA outpatients receiving adalimumab and etanercept treatment over a 4 year period (March 2003-October 2012) attending the Rheumatology Unit, University of Padua. Age, sex, onset age, disease and therapy duration were evaluated. The therapy efficacy was determined using the Bath Ankylosing Spondylitis Activity Score (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), the Health Assessment Questionnaire (HAQ), DAS28, the patient global assessment, the pain global assessment, the erytrocite sedimentation rate (ESR) and C-reactive protein (CRP). The percentage of patients in whom therapy interval administration was prolonged was also evaluated. Results: One hundred twenty-seven patients (79 male 62.2 %; median age 50.14±11.81 yrs; mean disease duration 11.9±8.35 yrs; mean follow-up 52.3±24.92 months) were treated with etanercept and adalimumab (respectively 48.8% and 51.2%). Average baseline and of treatment values were: BASDAI 51.05±22.30 vs BASDAI 26.70±19.55 (p<0.0001); BASFI 34.25±23.74 vs BASFI 16.85±10.51 (p<0.0001); HAQ 0.72±0.60 vs HAQ 0.36±0.22 (p<0.0001); DAS 28 3.10±1.22 vs DAS 28 2.17±0.92 (p<0.0001); patient global assessment 47.20±23.20 vs 26.11±18.23 (p<0.0001); patient pain assessment 41.09±21.44 vs 25.83±18.29 (p<0.0001); ESR 26.90±20.31 mm/1^h vs ESR 13.76±11.71 mm/1^h (p<0.0001); CPR 10.35±8.36 mg/l vs CPR 2.82±1.82 mg/l (p<0.0001). It was possible to extend the interval between injections in 54 (42.5%) of the patients whose responds to therapy was satisfactory, after a mean treatment of 11.84±5.69 months, with adalimumab and etanercept respectively 15.7% and 26.8%. The mean interval obtained was 3.05 weeks in adalimumab and 2.26 weeks in etanercept. Conclusions: A clinical, functional and bioumoral improvement was observed in both patients treated with adalimumab as well as etanercept. Treatment with anti-TNFα agents provokes a satisfactory prolonged, clinical response. It was possible to extend the interval between injections in a high percentage of PsA patients. Disclosure of Interest: None Declared